A Comparative Investigation into the Career Aspirations of Male and Female Secondary School Students in Khyber Pakhtunkhwa, Pakistan - Zeb, Alam; Ali, Arshad; Hussain, Mian Said (Annals of Human and Social Sciences, 2025)
Career aspiration is a key predictor in determining the career of students at secondary level. It affects both male and female students. This study aimed at comparative investigation of career aspirations among male and female secondary level students in Khyber Pakhtunkhwa, Pakistan. Objectives of the study were to find out the career aspirations of male and female students in secondary schools and to develop strategies for effective career planning of students at secondary level. Study’s design was quantitative. Its population was 30439 students. A sample of 380 was selected with stratified random sampling. A questionnaire was developed, validated and pilot tested for collecting data.. Data were gathered with self-administered questionnaires and analyzed with using mean scores, standard deviations and the chi-square test. Career aspirations of males were medical, engineering, computer and information technology. Career aspirations of females were teaching and medical. Both genders were having career aspirations of traditional careers. The study recommended strategies of career guidance in schools. Assistance of teachers and parents in selection of school subjects and career orientation sessions for effective career planning and aspirations of students.